2012
DOI: 10.5588/ijtld.11.0262
|View full text |Cite
|
Sign up to set email alerts
|

Integration of HIV testing in tuberculosis drug resistance surveillance in Kazakhstan and Kenya [Short communication]

Abstract: In Kenya and Kazakhstan, integration of human immunodeficiency virus (HIV) testing results into the routine surveillance of multidrug-resistant tuberculosis (MDR-TB) proved feasible and useful. The integration process improved overall data quality and data validation capacity, and integrated data are a useful addition to routine cohort and treatment outcome data. Besides their importance for individual patient care, they provide trends on the association of MDR-TB and HIV in the routine programme setting. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…An earlier study evaluating completeness of DST results among culture-positive TB patients in Kazakhstan found that the rate of missing records decreased from 32.3% to 7.2% from March 2009 to March 2010 after regional TB centers were provided with monthly notifications to complete and correct data. [ 14 ] Our findings suggest that the completeness of records has reduced again, due to the introduction of a revised TB register, which does not have checks in place yet.…”
Section: Discussionmentioning
confidence: 92%
“…An earlier study evaluating completeness of DST results among culture-positive TB patients in Kazakhstan found that the rate of missing records decreased from 32.3% to 7.2% from March 2009 to March 2010 after regional TB centers were provided with monthly notifications to complete and correct data. [ 14 ] Our findings suggest that the completeness of records has reduced again, due to the introduction of a revised TB register, which does not have checks in place yet.…”
Section: Discussionmentioning
confidence: 92%
“…Our survey found a prevalence of 1.8% MDR-TB among NSP which is lower than what was reported for Gujarat in 2007 (2.4%) [ 7 ]. The prevalence is lower than that reported from other high TB burden countries such as the former Soviet Union (ranged from 2.8% to 28.6%) [ 14 ], China (ranged from 3.8% to 14.7%) [ 15 , 16 ], and some low burden countries: Cameroon (6.67%) [ 17 ], Turkey (6.6%) [ 6 ] and Kenya (6.8%) [ 18 ]. All these surveys were done between 2008 and 2012 and appropriate guidelines were followed.…”
Section: Discussionmentioning
confidence: 74%
“…More investments should be made in improving data capturing to include data on HIV co‐infection in MDR‐TB (Klinkenberg et al . ).…”
Section: Discussionmentioning
confidence: 97%